Does the efficacy of neurodynamic treatments depend on the presence and type of criteria used to define neural mechanosensitivity in spinally-referred leg pain? A systematic review and meta-analysis - Tawanda Murape; Timothy R. Ainslie; Cato A. Basson; Annina Schmid (AOSIS, 2022)
Background: It remains unclear whether definite neural mechanosensitivity (NM) is required for neural mobilisations to be beneficial in people with spinally referred leg pain. Objective: To determine whether the efficacy of neural mobilisations in patients with spinally referred leg pain depends on the presence and type of criteria used to define NM. Method: PubMed, CINAHL, Cochrane Central Register of Controlled Trials, PEDro and Science Direct were searched from 1980 to March 2020. Randomised controlled trials evaluating the efficacy of neural mobilisations on pain and disability in spinally referred leg pain were included. Studies were grouped according to the certainty of NM into NMdefinite, NMunclear, NMuntested and NMabsent. Effects on pain and disability and subgroup differences were examined. Results: We identified 21 studies in 914 patients (3 NMdefinite, 16 NMunclear, 2 NMuntested, 0 NMabsent). Meta-analysis revealed medium to large effect sizes on pain for neurodynamic compared to control interventions in NMdefinite and NMunclear groups. For disability, neurodynamic interventions had medium to large effects in NMunclear but not NMdefinite groups. NMuntested studies could not be pooled. Conclusion: The nonexistence of studies in patients with negative neurodynamic tests prevents inferences whether neural mobilisations are effective in the absence of NM. The criteria used to define NM may not impact substantially on the efficacy of neural mobilisations. The mostly high risk of bias and heterogeneity prevents firm conclusions. Clinical implications: Neural mobilisations seem beneficial to reduce pain and disability in spinally referred leg pain independent of the criteria used to interpret neurodynamic tests.